Mopping up the labour shortage: the privatisation of waste management and gendered work reorganisation. (1st October 2008) - Melanie Samson
Abstract : This article explores the gendered nature of work reorganisation in Johannesburg's privatised Pikitup waste management utility. It establishes that feminist analysis requires an exploration of the historical production of gendered and racialised divisions of labour, the continuities and disjunctures that arise with privatisation, the consequences for men and women workers in the workplace and the home and the effects of men's gendered privileges. Because Pikitup's profit-generating strategy mapped onto a pre-existing gender division of labour, the all-male collection workforce was shielded from labour shortages that resulted in dramatic forms of work reorganisation in the feminised street cleaning sector. Male street cleaning workers experienced the same objective transformations in work organisation as their female counterparts. However, they were less compromised due to the power associated with their masculinity in both the workplace and the home, belying any notion of convergence of experience between male and female workers.